Modelo Prolab: “Qhali Kay, Farmacia Especializada en Mezclas Oncológicas y Nutrición Parenteral” - Salcedo Alvarez, Angela del Rocio (2024)
Cancer ranks as one of the leading causes of morbidity and mortality in Peru, aggravated by inadequate access to timely and appropriate treatments. Data from the National Institute of Statistics and Informatics (INEI) and the Ministry of Health (MINSA) indicate a rising incidence of cancer, with the unavailability of suitable treatments in both public and private healthcare facilities presenting a significant ongoing challenge. This project proposes the establishment of a specialized pharmacy dedicated to preparing oncological mixtures and parenteral nutrition, addressing the critical shortage of specialized services and enhancing access in Peru’s southern region. The World Health Organization (2024) report that the cancer burden is intensifying, with cancer deaths projected to reach 11.5 million by 2025. In this context, the initiative to create a network of pharmacies in Arequipa is not merely relevant but vital, as Arequipa acts as a pivotal center for patients from surrounding areas. The project hinges on the feasibility of setting up specialized facilities within compact spaces, leveraging the availability of appropriate venues. This infrastructure will adequately meet the escalating demand and improve the logistics of treatment distribution, thereby reducing costs and wait times. Financial viability is underpinned by projections of increasing cancer incidence and the consequent demand for specialized treatments, ensuring sustainable profitability and a profound impact on patients' quality of life